Production cost of transgenic corn in the first and second harvest in different regions in Brazil (Research, Society and Development, 2020)
Corn culture is one of the important economic segments of Brazilian agribusiness. The increase in corn production is related to increased productivity and in the cultivated area. In addition, the variation in productivity in the different Brazilian states is highlighted, which can be explained by the technological level of production. Therefore, the objective was to evaluate the production costs of eighteen producing regions to determine the cost of production in the first harvest in three agricultural years and in the second harvest in four agricultural years with transgenic corn, in addition to analyzing the influence of productivity on the cost of production. An exploratory research was carried out with data provided by the Companhia Nacional de Abastecimento. Statistical data were analyzed in the agricultural years of 2018, 2019 and 2020 in eighteen Brazilian municipalities. The region of Chapadão do Sul - MS, in both harvests, obtained the lowest production costs per bag of 60 Kg and per hectare were in Balsas - MA and Santo Ângelo - RS. The highest production costs per bag and per hectare in the 1st harvest were in the cities of Unaí - MG and Boa Vista - RR and the lowest costs per hectare were in Campo Mourão - PR and Sorriso - MT. The highest production costs per bag in the 2nd harvest were in Rio Verde - GO and Ubiratã - PR and per hectare were in Unaí - MG and Campo Mourão - PR.